Demonstrations as an essential component of the democratic system - Prianto, Yuwono; Nadilatasya, Putri Meilika; Nuzan, Namira Diffany; Burnama, Yustince (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Democracy, as a system of government based on popular sovereignty, places freedom of expression as a fundamental right of every citizen. One tangible manifestation of this right is demonstrations, which serve as an essential means of channeling public aspirations toward government policies. This study aims to analyze the role of demonstrations as an essential element in strengthening Indonesia"™s democratic system. The research employs a normative juridical method with a legal-philosophical and literature-based approach. The findings indicate that demonstrations play a strategic role in balancing the relationship between state authority and public participation while reinforcing democratic legitimacy. However, demonstrations often create tension between freedom of expression and public order, necessitating proportional legal regulations grounded in substantive justice. Drawing on the theories of John Stuart Mill, John Locke, and Gustav Radbruch, demonstrations should ideally be conducted peacefully, rationally, and responsibly to maintain harmony between citizens"™ rights and the public interest. Therefore, demonstrations must be regarded not as a threat but as a vital pillar of constitutional democracy in Indonesia